2006
DOI: 10.1590/s1677-04202006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects between supplemental ultraviolet-B radiation and heavy metals on the growth and biochemical characteristics of Spinacia oleracea L.

Abstract: The impact of supplemental UV-B (sUV-B) radiation and heavy metals: Cd (68 µmol.kg -1 soil) and Ni (68 μmol.kg -1 soil) singly and in combination was studied on photosynthetic and non-photosynthetic pigments, metabolites, enzyme activities, biomass accumulation and the net primary productivity of spinach (Spinacia oleracea L. var. All Green), a common leafy vegetable plant. Both the stresses individually and in combination resulted in the reduction of photosynthetic pigments, ascorbic acid, and catalase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…At 10ppm, 20ppm and 30ppm the dry weight are 0.040mg, 0.030mg, 0.020mg respectively than 0.135mg in control dry weight is decreased more than ZnSO 4 and CuSO 4 . The characteristic feature of toxicities in plant due to heavy metal chlorosis and reduction in net photosynthetic which leads to decrease plant growth and productivity (Sweta, 2006) It is concluded that Spinach (All Green) variety which can be cultivated at those areas at which heavy metals are present in soil or in the water used for irrigation as they showed some resistance against heavy metals treatment, which is proved by their data in germination %, seedling length, seedling fresh and seed ling dry weight parameters.…”
Section: Effect Of Heavy Metals On Seedling Dry Weightmentioning
confidence: 99%
“…At 10ppm, 20ppm and 30ppm the dry weight are 0.040mg, 0.030mg, 0.020mg respectively than 0.135mg in control dry weight is decreased more than ZnSO 4 and CuSO 4 . The characteristic feature of toxicities in plant due to heavy metal chlorosis and reduction in net photosynthetic which leads to decrease plant growth and productivity (Sweta, 2006) It is concluded that Spinach (All Green) variety which can be cultivated at those areas at which heavy metals are present in soil or in the water used for irrigation as they showed some resistance against heavy metals treatment, which is proved by their data in germination %, seedling length, seedling fresh and seed ling dry weight parameters.…”
Section: Effect Of Heavy Metals On Seedling Dry Weightmentioning
confidence: 99%
“…This reduction in the growth and photosynthetic pigments could be due to the disturbance in photosystem I and induced activity of chlorophyllase enzyme [32]. The protective function of anthocyanin against the stress conations is fairly clears [33]. Similarly, observations have been made in many plants species [34][35][36].…”
Section: Effect Of Strontium On Photosynthetic Pigmentsmentioning
confidence: 99%
“…Chlorophyll and carotenoids are the main core of energy production in green plants, and their amounts are significantly changed by environmental effects on plant metabolism (Shweta and Agrawal, 2006). The photosynthetic pigments are most likely to be damaged by air pollution.…”
Section: The Biochemical Characteristicsmentioning
confidence: 99%